Influence of nitrate salt solutions on seed germination dynamics of Withania coagulans (Stocks) Dunal, an important medicinal plant of the Indian Thar desert (Bangladesh Journal of Botany, 2019)
The effect of different concentrations (0.10, 0.25, 0.50, 0.75 and 1.0%) of nitrate salt solutions, viz. Ca(NO3)2, Co(NO3)2 and KNO3, on various aspects of fresh and one-year-old seeds and the seedling growth of Withania coagulans (Stocks) Dunal, is a critically endangered medicinal plant of the Indian Thar desert was dealt with. The maximum germination percentage in fresh and one-year-old seeds was observed in 1.0 and 0.10% Co(NO3)2 solutions, respectively. The maximum root: shoot ratio in seedlings from fresh and one-year- old seeds was observed in 0.75 and 0.50% of Ca(NO3)2 solutions, respectively.